Commercial Vehicle Production Flexibility Factors - Nascimento, Luis de Oliveira [UNESP]; Muniz, Jorge [UNESP]; Rocha, Henrique Martins; Naas, I; Vendrametto, O.; Reis, J. M.; Goncalves, R. F.; Silva, M. T.; VonCieminski, G.; Kiritsis, D. (Springer, 2016)
In the competitive commercial vehicles market, new products are developed continuously in order to attend specific demands and surplus complexity is incorporated gradually to the manufacturing assembly plants. In this context, it is mandatory that the manufacturers enable a high flexibility production level to attend specific demands with low costs and agility. This paper aims to analyze factors that influence the flexibility of commercial vehicles production and to propose a prioritization model for industrial productivity enablement projects, in order to improve the production flexibility in a trucks and buses assembly plant. Managers and technical staff of a commercial vehicles production plant (88 professionals) were interviewed and data analyzed by Incomplete Pairwise Comparison (IPC), a multicriteria decision method. Results lead the company to implement lean office projects, which created the condition to reduce 30% in the firm horizon of order placement, reducing the time-to-market and leading customer to have a higher product value-added perception, levering company's service level and competitiveness.
Keywords: Flexibility; Lean; Agility; Decision making